Perencanaan Strategis Unit Rawat Jalan RS Dokter Adam Talib Cikunir Bekasi untuk Meningkatkan Pendapatan - Fira Thiodorus; Cicilia Windiyaningsih; Nurhayati Nurhayati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
The Outpatient Unit is an important service unit that contributes to the hospital's revenue. However, at Adam Talib Cikunir Hospital, the number of patient visits has not yet reached the target, thus it is necessary to formulate a strategy to enhance competitiveness. This research aims to develop a strategic plan for the Outpatient Unit to improve service quality and increase its contribution to the hospital's revenue. The research uses a qualitative descriptive approach. Analysis is conducted through Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), SWOT analysis, and Quantitative Strategic Planning Matrix (QSPM). The IFE score of 2.44 and the EFE score of 2.41 place RS DAT Cikunir in Quadrant V of the IE Matrix, which means RS DAT Cikunir is in a Hold and Maintain position. The SWOT analysis generates several alternative strategies, and the QSPM prioritizes three strategies: enhancing specialized services (score 5,84), expanding services and digital promotion (score 5,66), and optimizing cooperation with BPJS and private insurance (score 5,38). The research concludes that improving specialized services, expanding services and digital promotions, as well as optimizing cooperation between BPJS and private insurance are the right strategies to enhance service quality, attract more patients, and strengthen the competitiveness of RS Dokter Adam Talib Cikunir amid competition in the healthcare sector.